2013
DOI: 10.1016/j.neuroscience.2012.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor performance asymmetries predict hand selection

Abstract: Handedness is most often measured by questionnaires that assess an individual’s preference for using a particular hand to perform a variety of tasks. While such assessments have proved reliable, they do not address the underlying neurobehavioral processes that give rise to the choice of which hand to use. Recent research has indicated that handedness associated with hemispheric specializations for different aspects of sensorimotor performance. We now hypothesize that an individual’s choice of which hand to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
59
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 76 publications
12
59
3
Order By: Relevance
“…However, the percentage of reaches into the contralateral hemispace with the dominant right arm were not as high as that observed for young adults in several previous studies 24,25 , even those with the same array of targets as we presented in our current study 6 . This difference in reaching pattern between young 6 and older adults (current study) could be attributed to the reported reduction in motor performance and motor transfer asymmetries with aging 26,27 . Consistent with this idea, neuroimaging studies have shown that, as people age, there is a considerable reduction of hemispheric asymmetry 28 .…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…However, the percentage of reaches into the contralateral hemispace with the dominant right arm were not as high as that observed for young adults in several previous studies 24,25 , even those with the same array of targets as we presented in our current study 6 . This difference in reaching pattern between young 6 and older adults (current study) could be attributed to the reported reduction in motor performance and motor transfer asymmetries with aging 26,27 . Consistent with this idea, neuroimaging studies have shown that, as people age, there is a considerable reduction of hemispheric asymmetry 28 .…”
Section: Discussioncontrasting
confidence: 83%
“…The rationale for this is that reaches that cross midline require more energy 22 , although some have also attributed the tendency to the greater demands of intrahemispheric visual-motor processing 23 . However, even in healthy adults this reaching pattern appears to be asymmetric, with the dominant arm making slightly more reaches into the contralateral hemispace 6,21,24 . In the current study, our findings for healthy aged matched control subjects are generally in agreement with these previous studies.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Handedness has also been described as an asymmetry in the time and/or accuracy associated with fine motor tasks (Annett et al 1979; Carson 1993; Carson et al 1990; Sainburg, 2005; Sainburg and Kalakanis, 2000). We have recently linked these two manifestations of handedness: We showed that hand preference changes for reaching to different locations in space can reverse, depending on which hand has the accuracy advantage (Przbyla et al, 2013). Thus, when reaching to a large number of targets across the workspace, certain locations show dominant arm advantages when subjects have visual feedback and nondominant arm advantages when reaching without visual feedback.…”
Section: Introductionmentioning
confidence: 99%